2002
DOI: 10.1007/s00210-002-0582-6
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline-induced contraction of human saphenous vein and human internal mammary artery: involvement of different α-adrenoceptor subtypes

Abstract: Although saphenous veins and internal mammary arteries are commonly used for coronary artery bypass grafting, only a very few comparative studies are available on alpha-adrenoceptor-mediated vasoconstriction in these vessels. Thus, we determined, in isolated rings from human saphenous vein and human internal mammary artery, contractile responses to noradrenaline (10(-8)-10(-4) M) in the absence and presence of the alpha-adrenoceptor antagonists yohimbine (alpha(2)-adrenoceptor antagonist, 10(-8)-10(-6) M), pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 22 publications
1
13
2
Order By: Relevance
“…Potency and E max of noradrenaline are in line with earlier reports on human IMA (EC 50 value of 560 vs. 660 nM) (Giessler et al, 2002). In contrast, Akrinor TM when applied alone was devoid of any vasoconstriction, suggesting absence of relevant α 1 -AR-agonistic activity.…”
Section: Discussionsupporting
confidence: 91%
“…Potency and E max of noradrenaline are in line with earlier reports on human IMA (EC 50 value of 560 vs. 660 nM) (Giessler et al, 2002). In contrast, Akrinor TM when applied alone was devoid of any vasoconstriction, suggesting absence of relevant α 1 -AR-agonistic activity.…”
Section: Discussionsupporting
confidence: 91%
“…The different effects of levosimendan on human arterial and venous preparations may be due to the different pathways Values are means ± s. e. NE norepinephrine; IMA internal mammary artery; SV saphenous vein; NS, not significant of intracellular calcium increase and the role of the magnitude of K ATP channels in this process in these two vessels. It has been reported that the involved alphaadrenergic receptors in mediating NE-induced contraction in IMA and SV are different [13]. Based on the obtained results, levosimendan might be considered as a partial selective arteriodilator.…”
Section: Discussionmentioning
confidence: 87%
“…Regional blood flow is regulated by the vasoconstrictive transmitter norepinephrine (NE) released from sympathetic postganglionic neurons, which contracts vascular smooth muscles. 10,11 Blood flow is also regulated by the vasodilatory substance NO that is released from vascular endothelial cells and relaxes vascular smooth muscles. 12,13 Thus, drugs that reduce NE release or binding, or drugs that increase NO, can be used used to alleviate conditions with poor blood flow, 14,15 including microvascular dysfunction.…”
Section: Introductionmentioning
confidence: 99%